Management of Working Production Assets As the Basis For the Formation of an Operational Strategy - Djurabayev Otabek Djurabayevich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
The production activities of an industrial enterprise are of great importance and are aimed at producing products based on the use of various resources and materials. Working capital management plays an important role in the operating activities of an enterprise, including the purchase of raw materials, supplies, fuel and electricity. Effective management of working capital helps improve production efficiency and ensures positive results. Working capital represents the necessary resources for the continuous operation of an enterprise, and their optimization contributes to the success of the enterprise. Thus, effective management of production activities and working capital is a key factor for the successful operation and development of industrial enterprises.